2020
DOI: 10.3201/eid2612.203386
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Bat Sarbecovirus Phylogenetically Related to SARS-CoV-2, Japan

Abstract: D uring the past 20 years, coronaviruses belonging to the genus Betacoronavirus have caused multiple human epidemic or pandemic diseases, including severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and coronavirus disease (COVID-19). Two viruses of the subgenus Sarbecovirus are severe acute respiratory syndrome coronavirus (SARS-CoV), which causes SARS, and SARS-CoV-2, which causes COVID-19. Although Rhinolophus spp. bats in Asia, Europe, and Africa are considered natural reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 15 publications
1
137
0
1
Order By: Relevance
“…An early report by Zhou et al identified a closely related SARSr-CoV genome sequence, RaTG13, which shared a 96% whole-genome sequence identity with SARS-CoV-2, indicating a probable bat origin of SARS-CoV-2 2 . Since then, more SARS-CoV-2-related viral genome sequences from bats have been reported from Eastern China 7 and Japan 8 , and from pangolins in China 9 , 10 . However, the immediate animal ancestor or progenitor virus, the equivalent of the >99% identical SARS-CoV sequences identified in civets during the SARS outbreak in 2003 11 , remains elusive for SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…An early report by Zhou et al identified a closely related SARSr-CoV genome sequence, RaTG13, which shared a 96% whole-genome sequence identity with SARS-CoV-2, indicating a probable bat origin of SARS-CoV-2 2 . Since then, more SARS-CoV-2-related viral genome sequences from bats have been reported from Eastern China 7 and Japan 8 , and from pangolins in China 9 , 10 . However, the immediate animal ancestor or progenitor virus, the equivalent of the >99% identical SARS-CoV sequences identified in civets during the SARS outbreak in 2003 11 , remains elusive for SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary trajectory of an evolved virus is difficult to analyse from nucleotide sequences because the data have complex multivariate structures with numerous dimensions 2 . Phylogenetic trees have long been used to present relationships in among sequences 3 and many studies on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 4 have employed them 58 , but they have two drawbacks. One is the decisive lack of falsifiability that ruins objectivity 9 , and the other is a lack of generality that makes it difficult to integrate with other data sources.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although there exists sequences homologous to the ORF10 protein in other closely related bat and pangolin CoVs, there are no experimentally derived crystallographic structures for the ORF10 protein. 10,11 Studies attempting to predict the secondary structural elements of this protein indicate one α-helix and, depending on the study, two β-strands. 12,13 The ORF10 protein also lacks significant levels of disorder; however, a short molecular recognition feature (MoRF) likely spans residues 3-7.…”
Section: Introductionmentioning
confidence: 99%